Comparative Antimicrobial Study of Different Parts of Ocimum americanum L., O. basilicum L. and O. sanctum L. in Comparison to Standard Antibiotics Collected from Dibrugarh, Assam - Chetia, J.; Saikia, L. R.; Upadhyaya, S.; Khatiwora, E.; Bawri, A. (Journal of Scientific Research, 2021)
Lamiaceae members are commonly used in ethno-medicinal practices of our country. The in vitro antibacterial and antifungal activity of various solvents extracts of different aerial parts of Ocimum americanum L., O. basilicum L. and O. sanctum L. wereassessed on standard bacterial and fungal strains using standard laboratory methods. Extracts from O. americanum have inhibitory activity against B. subtilis, B. cereus and S. aureus.Acetone extracts of O. basilicum and O. sanctum were found to be more potent being capable of exerting significant inhibitory activities against majority of the bacteria investigated. Acetone extract of young inflorescence of O. americanum showed highest antibacterial activity against B. cereus (14±1mm) which was also higher (10±1mm) than the inhibition of standard Clotrimazole (10mcg). Hot petroleum ether extract of mature leaves of O. basilicum showed highest activity against E. coli (16±2mm) which was also higher than the inhibition ofAmpicillin, Streptomycitin, Erythromycin.Petroleum ether extract of young leaves of O. sanctum recorded highest inhibition against P. vulgaris (20±2mm). Presence of tannins, flavonoids, saponins, phenols in all the parts of the plants. Use of different parts instead of using whole plant will help in sustainable management of these medicinal plants.